The effect of an education program on the knowledge level and attitudes about diabetes mellitus - doi:10.5020/18061230.2011.p322 - Fernanda Paola de Pádua Gandra; Kellen Cristine Silva; Cinara Fonseca Castro; Elizabethe Adriana Esteves; Luciana Neri Nobre (Universidade de Fortaleza, 2012)
Objective: To evaluate the impact of an education program on the knowledge level and attitudes about diabetes in diabetic patients. Methods: It was a before-and-after intervention study carried out in two moments: before and twelve months after implementation of the Diabetes Education Program (PED). We evaluated 23 patients with diabetes mellitus followed by two Basic Health Units from Diamantina-MG, Brazil. The data collection instrument was a semi-structured questionnaire with questions about personal data, educational level, disease definition, duration, causes, treatment, and difficulties in controlling it and the source of information on diabetes. The effect of the program on knowledge and attitudes was evaluated by comparing the number of correct answers before and after 12 months of its start, as well as changing attitudes about the disease. Results: We observed an increase in the number of correct answers on the diabetes symptoms and complications. The same occurred on the recognition of the importance of physical activity (27%) and on the self-application of insulin (40%) for treatments. In both moments, more than 50% of subjects reported having difficulty in the treatment of diabetes, and following the diet was the most referred. Only 4% answered correctly on the causes of diabetes in both moments. Conclusion: There was an improvement of the conceptual notions of the patients, especially on the definition of the disease, its symptoms and complications. Factors such as education level, age and income may have influenced the acquisition and incorporation of knowledge, changing it into concrete actions